Defining Poetics: A Dialogue between Western Theories and the Asian Philosophies in the Intimate Spaces of George Town, Penang Through Visual Interpretations and Cultural Analysis - Balaguru, Sonia Mancxia (MAJ - Malaysia Architectural Journal, 2021)
The great shift from intimate scale to mega projects has raised questions on the future of architecture in both Western and Eastern context. The research focuses on George Town, Penang – a city with a history dating back to 1800s which reflects the British’s presence on the island and the coalescence with the local cultures to create an integral piece of urban texture; now an architectural gem of the Southeast Asia. The research sets forward the concept of poetics in intimate spaces as a passion towards understanding the relationship between the intimacy of space and people. Its principle objective is to articulate theories and philosophies, in relation to the spatial experiences and the in-betweenness within the city. With the support of literatures, the discourse acknowledges the cognitive mapping of George Town as a way to depict the author’s perception of a place whilst expressing experience and personal impressions through affective illustrations. Upon the expression of experiences, the author decodes the spirit of place and reinterprets architectural expressions of voids through typical elements of a shophouse dwelling: the window, the courtyard and the walkways. For the author, these are the elements that form the mental image of George Town hence expressing the personal perception of place.